Formas de resistência de crianças contra tecnologias pedagógicas que tendem a subjugar a infância : o ensino de língua inglesa - Silva, Priscila Aline Rodrigues (2017)
This research was developed within the Master Degree Program in Education of the Federal University of Mato Grosso, in Rondonópolis city (PPGEdu/UFMT/CUR), in the line of research Languages, culture and knowledge construction process: historical and contemporary perspectives. It was constructed based on the discussions proposed within the Study Group Childhood, Youth and Contemporary Culture (GEIJC, Grupo de Estudos Infância e Juventude na Cultura Contemporânea) and it aims to reflect about childhood and its subjects. The socially built concepts of child and childhood demarcate the position of children in our society affecting the relationship between adults and children and also perpetuating an adultocentric world order. Thus, this research understands childhood as a permanent structural society’s category, and it draws the historical path to construction of the childhood representations, children’s rights and Brazilian education policies. This study is sustained by the Sociology of Childhood and it intends to understand children subordination and their multiples manifestations of resistance against adultocentric world order. Furthermore, school is the place where children spend most of their time. It is also their place of work and where they are submitted to diverse forms of subordination. Thus, the main goal of this investigation is to understand how children resist to pedagogical technologies imposed by adults and reflect about their attempts to insert their cultures within the English language teaching and learning process as a way to demarcate their social acting. So, we developed a field research of ethnographic type and we registered the primary and secondary adjustments manifested along English language classes. The results revealed, among other inferences, the need to rethink the adultocentric teaching practices and the necessity to promote a pedagogical practice which recognizes child as the protagonist of learning process especially because of their creativity and their resistances against adult’s subordination.